A biophysical, biochemical and serological study of selected members of the enteroviruses - Smith, Martin Sidney (Department of Biological Sciences, 2020)
The purpose of this investigation was to study the biophysical and biochemical properties of some of the enteroviruses. Previous work in this laboratory on several members o.f this large sub-group of the Picornaviruses had emphasised the importance of a more detailed examination of some of the surface properties of representative strains of enteroviruses, by currently available techniques.